Analisis Konsumsi Budaya Populer Jepang pada Aspek Kehidupan Sosial Mahasiswa - Maheswara Hermadhito Prapancha; Hikmal Fajar Fardyan; Jhon Daniel Manurung; Sri Mulyeni (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Japanese popular culture, such as anime, manga, cosplay, and J-Pop music, has become part of the daily lives of Indonesian students along with the development of technology and digital media. The consumption of Japanese popular culture not only serves as a form of entertainment but also influences aspects of social interaction, identity formation, and how to express oneself in social environments. This study aims to analyze the influence of Japanese popular culture consumption on the social lives of students. Writers used a qualitative method with literature study techniques. Data were obtained through searching and analyzing various previous scientific journal articles on relevant topics published in the last ten years. The results of the study indicate that consumption of Japanese popular culture has various impacts on the social lives of students. On the one hand, Japanese popular culture can broaden cultural horizons, strengthen social interactions through communities and fandoms, and increase interest in learning the Japanese language and culture. On the other hand, there is the potential for negative impacts on consumers, such as consumptive behavior, excessive fanaticism, and a tendency to limit social interactions outside of specific interest groups. Therefore, critical awareness and a selective attitude are needed in consuming Japanese popular culture so that the received influence is positive and does not neglect local social and cultural values.